2014
DOI: 10.1111/pcn.12155
|View full text |Cite
|
Sign up to set email alerts
|

Parental quality of life and depressive mood following methylphenidate treatment of children with attention‐deficit hyperactivity disorder

Abstract: Aim: This naturalistic study investigated the associations between quality of life and depressive mood in parents and symptom changes in attention-deficit hyperactivity disorder (ADHD) children. Methods:At baseline and at weeks 4 and 8, the parents evaluated their children, who were receiving treatment with osmotic-release oral system methylphenidate (mean dosage 36.3 ± 15.5 mg/day), using the Swanson, Nolan, and Pelham -Fourth Edition (SNAP-IV-18) scale. The parents evaluated themselves using the Beck Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In general terms, QoL may be thought of as a multidimensional construct incorporating an individual’s subjective perception of physical, emotional, and social well being, including both a cognitive (satisfaction) and an emotional component (happiness) ( 9 ). Although QoL is influenced by many proximal (e.g., family and friendship) and distal (e.g., socioeconomic and cultural) factors, the presence of a chronic illness has been considered as one of the most potent risk factors for worse QoL scores ( 4 , 9 14 ). Many authors have reported that chronic illnesses have an impact on many different aspects of the patient’s lives, which go beyond the core symptoms and impact their QoL ( 4 , 9 , 11 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general terms, QoL may be thought of as a multidimensional construct incorporating an individual’s subjective perception of physical, emotional, and social well being, including both a cognitive (satisfaction) and an emotional component (happiness) ( 9 ). Although QoL is influenced by many proximal (e.g., family and friendship) and distal (e.g., socioeconomic and cultural) factors, the presence of a chronic illness has been considered as one of the most potent risk factors for worse QoL scores ( 4 , 9 14 ). Many authors have reported that chronic illnesses have an impact on many different aspects of the patient’s lives, which go beyond the core symptoms and impact their QoL ( 4 , 9 , 11 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although QoL is influenced by many proximal (e.g., family and friendship) and distal (e.g., socioeconomic and cultural) factors, the presence of a chronic illness has been considered as one of the most potent risk factors for worse QoL scores ( 4 , 9 14 ). Many authors have reported that chronic illnesses have an impact on many different aspects of the patient’s lives, which go beyond the core symptoms and impact their QoL ( 4 , 9 , 11 14 ). In studies using the World Health Organization Quality of Life-Bref Form (WHOQOL-Bref), one of the most used instruments to assess QoL, the scores are frequently lower in patients with chronic diseases, such as diabetes ( 9 , 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADHD needs to be understood and managed within a biopsychosocial paradigm that gives cognizance to the interaction between biological, psychological, and social variables [47] particularly those impacting the quality of relationship between the caregiver and the child. of life [48][49][50][51], psychological disorders [52]. These studies do suggest that caregivers of children with ADHD tend to endorse high levels of burden compared to controls [53].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the discontinuation of ADHD medications has been associated with suboptimal control of symptoms, increasing the likelihood of harmful and serious behaviors including social adversity, academic difficulties, behavioral problems, and poor economic, social, and emotional well-being ( 28 29 30 ). In addition, family and associated community members can be influenced by these adverse consequences as well ( 31 32 ), which could not be measured in the current study because the data from the Korean HIRA claims database were not allowed to link with any information of their family members. In previous studies, changes in parenting stress and parental quality of life were measured during the 8-week treatment with OROS-MPH in children and adolescents with ADHD.…”
Section: Discussionmentioning
confidence: 99%